A systematic review of the application of enzyme-based biosensors as a preliminary screening method for environmental monitoring and food safety - Mohd Khalizan Sabullah; Rahmath Abdullah; Roslina Jawan; Lucky Goh Poh Wah; Hartinie Marbawi; Syed Umar Faruq Syed Najmuddin; Jualang Azlan Gansau; Mohd Yunus Syukorb, Mohd Nazri Abdul Rahman (UTM Press, 2024)
In this article, the latest discoveries in the development of biosensors based on enzyme inhibition are reviewed. Due to their excellent selectivity and sensitivity, they represent a significant alternative method to conventional analytical methods; which is a method of analysis that only relies on the generation of instrumentation data without any preliminary screening. Basically, biosensors are able to convert biological activity into a quantifiable signal. These enzyme inhibition-based biosensors have a wide range of applications in the fields of environmental safety, food safety, and clinical analysis since toxic substances containing heavy metals and pesticides are the most effective inhibitors of enzymes. This paper is aimed at exploring the methods used and the sensitivity to various inhibitors for biosensors based on the inhibition of enzymes such as glucose oxidase, urease, tyrosinase, cholinesterase, and other enzymes.